Improved Antitumor Activity of a Therapeutic Melanoma Vaccine through the Use of the Dual COX-2/5-LO Inhibitor Licofelone - Neumann, Silke; Shirley, Simon A.; Kemp, Roslyn A.; Hook, Sarah M. (Frontiers in Immunology, 2016)
Immune-suppressive cell populations impair anti-tumor immunity and can contribute to the failure of immune therapeutic approaches. We hypothesized that the non-steroidal anti-inflammatory drug (NSAID) licofelone, a dual COX-2/5-LO inhibitor, would improve therapeutic melanoma vaccination by reducing immune-suppressive cell populations. Therefore, licofelone was administered after tumor implantation, either alone or in combination with a peptide vaccine containing a long tyrosinase-related protein (TRP)2-peptide and the adjuvant α-galactosylceramide, all formulated into cationic liposomes. Mice immunized with the long-peptide vaccine and licofelone showed delayed tumor growth compared to mice given the vaccine alone. This protection was associated with a lower frequency of immature myeloid cells (IMCs) in the bone marrow (BM) and spleen of tumor-inoculated mice. When investigating the effect of licofelone on IMCs in vitro, we found that the prostaglandin E2-induced generation of IMCs was decreased in the presence of licofelone. Furthermore, pre-incubation of BM cells differentiated under IMC-inducing conditions with licofelone reduced the secretion of cytokines interleukin (IL)-10 and -6 upon LPS stimulation as compared to untreated cells. Interestingly, licofelone increased IL-6 and IL-10 secretion when administered after the LPS stimulus, demonstrating an environment-dependent effect of licofelone. Our findings support the use of licofelone to reduce tumor-promoting cell populations.